Metabolomic and transcriptomice analyses of flavonoid biosynthesis in apricot fruits - Chen, Yilin; Li, Wenwen; Jia, Kai; Liao, Kang; Liu, Liqiang; Fan, Guoquan; Zhang, Shikui; Wang, Yatong (Frontiers in Plant Science, 2023)
Flavonoids, as secondary metabolites in plants, play important roles in many biological processes and responses to environmental factors. Apricot fruits are rich in flavonoid compounds, and in this study, we performed a combined metabolomic and transcriptomic analysis of orange flesh (JN) and white flesh (ZS) apricot fruits. A total of 222 differentially accumulated flavonoids (DAFs) and 15855 differentially expressed genes (DEGs) involved in flavonoid biosynthesis were identified. The biosynthesis of flavonoids in apricot fruit may be regulated by 17 enzyme-encoding genes, namely PAL (2), 4CL (9), C4H (1), HCT (15), C3'H (4), CHS (2), CHI (3), F3H(1), F3'H (CYP75B1) (2), F3'5'H (4), DFR (4), LAR (1), FLS (3), ANS (9), ANR (2), UGT79B1 (6) and CYP81E (2). A structural gene-transcription factor (TF) correlation analysis yielded 3 TFs (2 bHLH, 1 MYB) highly correlated with 2 structural genes. In addition, we obtained 26 candidate genes involved in the biosynthesis of 8 differentially accumulated flavonoids metabolites in ZS by weighted gene coexpression network analysis. The candidate genes and transcription factors identified in this study will provide a highly valuable molecular basis for the in-depth study of flavonoid biosynthesis in apricot fruits.